Functional guarantees: a new service paradigm. (14th January 2008) - Gupta, Aparna; Wallace, William A.; Sondheimer, Norman K.
Equipment service sector supports a nation's infrastructure. Improved diagnostics?prognostics technologies have enabled aggressive equipment producers to offer a new service ? a long-term guarantee on the operation of a product for a fee. Without a rigorous framework for managing these guarantees, the producer is exposed to extensive risks, resulting in serious losses. In this article, we formulate a conceptual framework for the design and delivery of a new service paradigm, Functional Guarantees. In Functional Guarantees, producers sell a service of providing well-defined 'functionality' from a physical equipment. As the core of the framework, integrated risk management enables viable delivery of the required quality of functionality from the equipment. The framework utilises operational learning and feedback mechanisms for operational risk management. For long-term sustainability and viability, strategic analysis integrally assesses the impact of a portfolio of service guarantees. The framework allows the producer to meet customers' needs and reduce risk of loss, while constantly looking toward improving profitability.